Islamic ethics for mediation: a maqāṣidic analysis - Amanullah, Muhammad (The Islamic Cultural Centre and London Central Mosque, 2018)
Courts all over the world are overwhelmed with so many different kinds of cases that resolution of disputes for them takes long periods of time. Additionally, the resolution of these cases is costly. Therefore, dispute resolution outside the court--which is less costly and takes less time—is used alternatively.An important mode of this resolution is mediation. Many organizations have been established for mediation. These organizations have developed their code of ethics for mediation. Islam also prescribes numerous ethics for mediation. Using descriptive and analytical methods, and based on certain Qur’ānic verses and aḥādīth of the Prophet (pbuh), this paper intends to discuss certain important ethics of mediation in the light of the higher objectives of Sharī‛ah (maqāṣid al- Sharī‛ah).This paper may conclude that implementation of Islamic ethics for mediation causes preservation of higher objectives of Sharī‛ah. On the other hand, neglecting these ethics may cause destruction of these objectives.